Ginsenoside Rd promotes omentin secretion in adipose through TBK1-AMPK to improve mitochondrial biogenesis via WNT5A/Ca2+ pathways in heart failure - Wan, Shiyao; Cui, ZeKun; Wu, Lingling; Zhang, Fan; Liu, Tao; Hu, Jingui; Tian, Jiangwei; Yu, Boyang; Liu, Fuming; Kou, Junping; Li, Fang (Redox biology, 2023)
Ginsenoside Rd is an active ingredient in Panax ginseng CA Mey and can be absorbed into the adipose tissue. Adipokines play an important role in the treatment of cardiovascular diseases. However, the potential benefit of Rd on heart failure (HF) and the underlying mechanism associated with the crosstalk between adipocytes and cardiomyocytes remains to be illustrated. Here, the results identified that Rd improved cardiac function and inhibited cardiac pathological changes in transverse aortic constriction (TAC), coronary ligation (CAL) and isoproterenol (ISO)-induced HF mice. And Rd promoted the release of omentin from the adipose tissue and up-regulated omentin expression in lipopolysaccharide (LPS)-induced 3T3-L1 adipocytes. Further, Rd could increase TBK1 and AMPK phosphorylation in adipocytes. And also, the TBK1-AMPK signaling pathway regulated the expression of omentin in LPS-induced adipocytes. Moreover, the omentin mRNA expression was significantly decreased by TBK1 knockdown in LPS-induced 3T3-L1 adipocytes. Additionally, molecular docking and SPR analysis confirmed that Rd had a certain binding ability with TBK1, and co-treatment with TBK1 inhibitors or TBK1 knockdown partially abolished the effect of Rd on increasing the omentin expression and the ratio of p-AMPK to AMPK in adipocytes. Moreover, we found that circulating omentin level diminished in the HF patients compared with healthy subjects. Meanwhile, the adipose tissue-specific overexpression of omentin improved cardiac function, reduced myocardial infarct size and ameliorated cardiac pathological features in CAL-induced HF mice. Consistently, exogenous omentin reduced mtROS levels and restored ΔψM to improve oxygen and glucose deprivation (OGD)-induced cardiomyocytes injury. Further, omentin inhibited the WNT5A/Ca2+ signaling pathway and promoted mitochondrial biogenesis function to ameliorate myocardial ischemia injury. However, WNT5A knockdown inhibited the impairment of mitochondrial biogenesis and partially counteracted the cardioprotective effect of omentin in vitro. Therefore, this study indicated that Rd promoted omentin secretion from adipocytes through the TBK1-AMPK pathway to improve mitochondrial biogenesis function via WNT5A/Ca2+ signaling pathway to ameliorate myocardial ischemia injury, which provided a new therapeutic mechanism and potential drugs for the treatment of HF. •Ginsenoside Rd improved CAL, ISO and TAC-induced HF by promoting the release of omentin.•Ginsenoside Rd promoted omentin secretion in adipose through TBK1-AMPK pathway.•Omentin ameliorated OGD and CAL-induced HF through promoting mitochondrial biogenesis via WNT5A/Ca2+ pathway.